Routine Intraoperative Forced-Air Warmer Usage in Prevention of Perioperative Hypothermia: To Use or Not to Use in Daycare Breast Lumpectomy? - Nadia HI.; Raha AR. (Department of Surgery, UKM Medical Centre, 2015)
Intraoperative active warming in daycare surgery may be least popular compared to major elective surgeries due to the lesser risk of perioperative hypothermia. This prospective, single blind, randomized, controlled trial in daycare breast lumpectomy was done to evaluate the routine use of intraoperative forced-air warmer in the presence of other warming modalities in prevention of perioperative hypothermia. Fifty patients were randomized into two groups; Group 1 received forced-air warmer and Group 2 received a standard cotton thermal blanket. Both groups received circulating-water mattress. Intraoperatively, all patients received pre-warmed intravenous fluid with an in-line warmer. Ear and ambient temperature was recorded using infrared ear thermometer and digital thermo-hygrometer respectively. Measurement was done before induction, every 15 minutes intraoperatively, upon arrival in recovery room and 30 mins later, postoperatively. All patients were normothermic prior to induction of anaesthesia. During the initial half an hour post-induction, both groups mean core temperature decreased at approximately 0.5˚C. Both showed no statistical difference in mean core temperature (0.04 ˚C) within the initial half an hour. The next half an hour, both groups had approximately 0.2˚C decrement but this time, Group 2 had a slightly higher mean core temperature than Group 1 which maintained until the end of surgery. Overall, within the initial one hour post-induction of GA, there was a drop of 0.7˚C and 0.6°C in Group 1 and Group 2 respectively, however the difference in final mean core temperature between the two groups was 0.05°C and it was not statistically significant (p value < 0.05). None of the patients experienced intraoperative hypothermia (< 36˚C) and all remained in the normothermic range with no shivering or sense of feeling cold, postoperatively. The results of the present study found no significant difference in the changes of final core temperature with or without the usage of intraoperative forced-air warmer in the presence of other warming measures in daycare breast lumpectomy.